The Effect of Current Ratio and Debt to Asset Ratio on Net Profit Margin at PT. Kimia Farma Tbk Period 2018-2022 - Octovian, Reza; Mardiati, Dijan; Winarsa, Hendra (Peneliti.net, 2024)
This research aims to determine the influence of Current Ratio (CR) and Debt To Asset Ratio (DAR) on Net Profit Margin (NPM). The method used is a descriptive analysis study with a quantitative approach method. The data used is secondary data obtained from the financial reports. The data analysis techniques used are descriptive statistical analysis, classical assumption testing, multiple linear regression and hypothesis testing. The partial results of this research are that. The Current Ratio has a tcount of 2.405 where the value is 2.405 > 2.306 and the significant value is 0.047 where the value is 0.047 < 0.05. So Ho1 is rejected and Ha1 is accepted, which means that the Current Ratio has a significant effect on the Net Profit Margin and Debt To Asset Ratio which has a t-count of -0.116 where the value is -0.116 < 2.306 and the significant value is 0.911 where the value is 0.911 > 0.05. So Ho1 is accepted and Ha1 is rejected, which means the Debt To Asset Ratio has no significant effect on Net Profit Margin. So that F count (0.017) > F table (4.740) and systematically a significance value of 0.984b is obtained. Because the significance value (0.984b)> significance level 0.05. Thus, Ho is accepted and H3 is rejected. This shows that there is no significant influence of the Current Ratio, Debt to Asset Ratio on Net Profit Margin. The coefficient of determination (R Square) is 0.005 or 5.00%. This means that 5.00% of the dependent variable, namely Net Profit Margin, can be explained or influenced by the independent variables (Current Ratio and Debt to Asset Ratio). Meanwhile, the remaining 95.00% is explained by other variables not examined in this research.